Detailed Precision of Computed Tomography Angiography Compared to Invasive Angiography in Different Coronary Vessels: Overestimate, Underestimate, or Concordance? - TM Haykal; Elen Elen; Celly A. Atmadikoesoemah; Abhirama N Putra; Andrew Parlautan; Wendy M Saragih; Manoefris Kasim (The Indonesian Heart Association, 2018)
Background: Quantitative analysis of stenosis lesions by Computed Tomography angiography (CTA) show good correlation with Invasive Coronary Angiography (ICA) examination. However, detailed precision whether CTA overestimate or underestimate have not been explored thoroughly. Objectives: This research is performed to analyze the precision of CTA compared to ICA. Materials & Methods: There are 195 patients examined by both CTA and ICA from October 2014 until December 2015 in our hospital. CTA was analyzed by a team of cardiovascular imaging cardiologists. Quantitative grading of stenosis was determined visually using 2014 Society of Cardiovascular Computed Tomography (SCCT) guidelines classification. Quantitative measurement of stenosis during ICA was classified with the same criteria so that it can be comparable. The final comparison of both tests was classified as concordance, overestimate and underestimate. Results: Lesion of stenosis was found in 573 coronary vessels. Coronary vessels are significantly associated with detailed precision of quantitative analysis comparison in CTA and ICA. LM coronary stenosis quantification from CTA is predominantly overestimate (concordance in 6% vessels and overestimate in 75.9% vessels), while stenosis analysis by CTA in other major coronary vessels is spread without conspicuous domination (p<0.001). Sensitivity, specificity, PPV, and NPV of CTA to detect obstructive lesion (stenosis ≥ 50%) found by ICA is 81.4%, 80.4%, 73.9%, and 86.3%, respectively (780 vessels). Conclusions: Degree of stenosis in LM is predominantly overestimate by CTA. The precision of stenosis grading in CTA in different coronary vessels is not the same. Abstrak Latar Belakang: Analisis kuantitatif lesi stenosis pada pembuluh koroner menggunakan modalitas Computed Tomography Angiography (CTA) memiliki korelasi yang baik dengan pemeriksaan Invasive Coronary Angiography (ICA). Namun, presisi CTA terhadap ICA masih belum tereksplorasi dengan baik. Terutama dari sisi apakah CTA menunjukkan presisi yang overestimate atau underestimate. Tujuan: Penelitian ini dilakukan untuk menganalisis presisi CTA terhadap ICA dalam mendeteksi lesi stenosis pada pembuluh koroner. Metode Penelitian: Terdapat 195 pasien yang diperiksa menggunakan CTA dan ICA sejak Oktober 2014 hingga Desember 2015 di RS Jantung dan Pembuluh Darah Harapan Kita, Jakarta. Analisis kuantitatif CTA dilakukan oleh tim kardiolog pencitraan kardiovaskular. Klasifikasi derajat stenosis ditentukan secara visual menggunakan pedoman dari Society of Cardiovascular Computed Tomography (SCCT) 2014. Analisis kuantitatif lesi stenosis dari pemeriksaan ICA diklasifikasikan menggunakan pedoman yang sama sehingga keduanya dapat diperbandingkan. Data hasil perbandingan kedua modalitas diklasifikasikan sebagai concordance, overestimate dan underestimate. Hasil Penelitian: Lesi stenosis ditemukan pada 573 pembuluh koroner. Pembuluh koroner yang berbeda secara signifikan berhubungan dengan perbandingan klasifikasi analisis semi-kuantitatif CTA dan ICA. Pembuluh koroner LM terutama menunjukkan lesi dengan kategori overestimate (75.9%). Sementara analisis stenosis pada pembuluh koroner lainnya tidak menunjukkan perbedaan yang mencolok (p < 0,001). Sensitivitas, spesifisitas, PPV, dan NPV CTA dalam mendeteksi lesi koroner obstruktif (stenosis ≥50%) terhadap ICA adalah sebesar 81.4%, 80.4%, 73.9%, dan 86.3% (780 pembuluh kroner). Kesimpulan: Analisis stenosis semi-kuantitatif pada LM terutama adalah overestimate berdasarkan pemeriksaan CTA. Presisi analisis perbandingan derajat stenosis CT angiografi pada setiap pembuluh koroner tidak sama.